Automation of Work Processes at Ukrainian Sorting Stations - Oleh, Strelko; Hanna, Kyrychenko; Yulia, Berdnychenko; Svitlana, Hurinchuk (International Journal of Engineering and Technology, 2018)
The article analyses the existing options for improving sorting stations operation by implementing informational support and automated systems as well as the development of new ideas to solve this issue. The study of this theme makes it possible to improve all basic indicators of station operation, the directorate and the railway as a whole. This study is a scientific problem to be reasonably considered with a systematic approach. The problem of sorting stations description as a complex facility of automation in the design systems of unified automated control systems has been considered. The analysis of up-to-date information systems and technologies being utilized at sorting stations of Ukraine has been carried out. Functional capabilities to be achieved while integration of the â€œAutomated control systemâ€ into the ASFTO UZ â€“ (e) have been achieved. Directions for further development of automated subsystem â€œDynamic work of the railway junctionâ€ requiring scientific researches in solving complex tasks for providing communication between the station wagon and the departure (transport document) have been determined. It has been determined that the further development of automated subsystem â€œDynamic work of the railway junctionâ€ was impossible without interaction with the feeder lines model, because all sorting stations perform a large amount of work with the participation of feeder lines.Â Â